Cover Picture: Highly Selective and Immortal Magnesium Calixarene Complexes for the Ring‐Opening Polymerization of rac‐Lactide (ChemCatChem 7/2014). Issue 7 (July 2014) - Walton, Mark J.; Lancaster, Simon J.; Redshaw, Carl
<x xml:space="preserve">Abstract</x> Cold‐blooded catalysis The cover represents work in collaboration between the University of Hull and the University of East Anglia. The image shows a crocodile with a cavernous mouth as a metaphor for the metal catalysts used. The reptile is swallowing whole cyclic monomers, ring opening them and excreting a polymeric product. The 2 D NMR backdrop illustrates the innovative and hugely convenient approach we have taken for facile stereochemical assignment. In their Full Paper on p. 1892 ff., M. J. Walton, S. J. Lancaster, and C. Redshaw describe their immortal magnesium calixarene complexes for the ring‐opening polymerization of rac‐lactide.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>